Pengaruh Financial Stress dan Pengelolaan Anggaran Terhadap Perilaku Keuangan Masyarakat dengan Dukungan Sosial Sebagai Variabel Intervening - Fadhila, Novi; Elvionita, Nadia (Journal Research of Economic and Bussiness, 2025)
Some of the economic problems that are currently rife in Indonesia include unemployment, poverty, prices, profits, inflation, debt, economic systems, political economy, welfare and economic growth, so this study aims to analyze the effect of financial stress and budget management on the financial behavior of the community in West Binjai, with social support as an intervening variable. The research is motivated by the phenomenon of low financial awareness, high levels of financial stress, and lack of social support in financial decision-making among the community. A quantitative associativecausal approach was employed, with data collected through questionnaires distributed to 100 respondents residing in West Binjai. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results indicate that both financial stress and budget management significantly influence financial behavior, directly and indirectly through social support as an intervening variable. Social support was found to strengthen the influence of both independent variables on financial behavior. This research provides theoretical contributions to the development of personal financial management literature and practical implications for local communities and governments in improving financial literacy and well-being. Keywords: Financial Stress, Budget Management, Financial Behavior, Social Support